An Atypical Cutaneous Reaction to Rivastigmine Transdermal Patch. (11th January 2011) - Grieco, T.; Rossi, M.; Faina, V.; De Marco, I.; Pigatto, P.; Calvieri, S.
Abstract : Rivastigmine is a cholinesterase inhibitor which improves cognitive function and is currently being used in patients with mild to moderate Parkinson's and Alzheimer's dementia. This drug can be given orally or topically, as transdermal patch. The latter form is currently used for most excellent compliance and few side effects. The most common cutaneous side effects are irritative dermatitis. We report the second case of active sensitization by the rivastigmine-patch in a patient suffering from Alzheimer's dementia.